A formação do professor dos anos iniciais do ensino fundamental no movimento de organização do ensino de frações: uma contribuição da atividade orientadora de ensino - Perlin, Patrícia (2014)
This work is the product of a project developed within the research line LP1 - Training, Knowledge and Professional Development of the Postgraduation Program on Education, of the Federal University of Santa Maria. The main objective was to investigate the training of teachers who teach mathematics in the early years of Elementary School in the context of the organization of fractions teaching for the fifth grade. To achieve it, we followed a teacher who teaches mathematics in the early years, participant of the PPOE / OBEDUC / CAPES project, in the movement of organization of fractions teaching, according to the Teaching Guiding Activity perspective - AOE (MOURA, 1996a, 1996b, 2001 2010).The specific objectives were deployed in formative and investigative. The first were aimed at the appropriation of theoretical and methodological assumptions that guided the actions of the research such as the Historical-Cultural Theory (VYGOTSKY, 1989, 1994, 2010, 2012), Activity Theory (LEONTIEV, 1978, 1983, 2012) and Teaching Guiding Activity, and also regarding the training of teachers of basic education (Cunha, 1999; PEPPER, 2007, 2009; LOPES, 2009; MOURA, 2000). The investigative objectives were: to investigate to what extent the AOE can become a general mode of action of the organization for the education of the teacher for the early years of elementary school; and identify factors that determine the change in the work quality of the teacher involved in this movement. The data were collected in 2013 in meetings recorded in audio and video, daily records and a semi-structured questionnaire. These data constituted episodes (MOURA, 1992) whose analysis showed that AOE can become the teacher training general organizational mode in the early years since: it is understood by the teacher as a possible way of overcoming the way mathematics has been traditionally taught; the teacher uses the theoretical assumptions which guide this methodological-theoretical proposition; and he/she is in teaching activity. Likewise, the factors that might determine the change in the teacher work quality, identified in the context of this research, were: mathematical learning; teaching learning and the new senses attributed to the teaching practice.